2020
DOI: 10.26682/sjuod.2020.22.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Compartive Evalution of A New Endodontic Irrigation Solution –apple Vinegar, Ginger Oil And Sodium Hypochlorite to Remove The Smera Layer by Scaning Electron Microscope Study

Abstract: Introduction: A three dimensional seal is the one of main steps in the successful root canal treatment .The smear layer that has been created on the dentinal wall during root canal instrumentation should be removed by using irrigation solution. Irrigation solution should be always used with mechanical preparation of root canal system as an important part for successful endodontic treatment Aim: The aim of this in vitro study was to compare the efficacy of four irrigating solutions in removing the smear layer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The results of the current study demonstrated that NaOCl group revealed the least mean of PBS with different root sections (Coronal, Middle, and apical) followed by EDTA group whereas, MTAD group revealed the greatest mean of PBS with different root sections. One way analysis of variance showed (1). Also, means of PBS for different sections (Coronal, Middle, and apical) with in the same group were compared, and similar results were noted in all experimental groups where, the greater mean of PBS was in the coronal section followed by middle section while, the lesser mean of PBS was in the apical section.…”
Section: Resultssupporting
confidence: 53%
“…The results of the current study demonstrated that NaOCl group revealed the least mean of PBS with different root sections (Coronal, Middle, and apical) followed by EDTA group whereas, MTAD group revealed the greatest mean of PBS with different root sections. One way analysis of variance showed (1). Also, means of PBS for different sections (Coronal, Middle, and apical) with in the same group were compared, and similar results were noted in all experimental groups where, the greater mean of PBS was in the coronal section followed by middle section while, the lesser mean of PBS was in the apical section.…”
Section: Resultssupporting
confidence: 53%
“…Endodontics research is directed to develop strategies for replacing the synthetic chemical irrigating solutions with biomaterials that meet the cleaning and therapeutic irrigation objectives and minimize the physically and chemically induced damage (20) . Natural irrigation products such as chitosan, chitosan nano-particles, and apple vinegar were proved proper microbial disinfection, removing tissue residues, and completely clean the root canal wall off the smear layer (6,7,10,11) . Thus, this study was directed to evaluate those newly proposed irrigants in relation to the gold stander and more contemporary chelating agent EDTA when used as final irrigating solutions.…”
Section: Discussionmentioning
confidence: 99%
“…It is known to have bactericidal effect towards microorganisms correlating with endodontic infections as Enterococcus faecalis and Staphylococcus aureus (6) . Apple vinegar was reported to be eligible for smear layer cleanliness that covers the root canal wall disserve the dentinal tubule promoted better cleaning with interaction mechanism comparable to that of EDTA on mineral content of intraradicular dentin (7) .…”
Section: Introductionmentioning
confidence: 99%
“…Both coronal, and apical surfaces of each section were observed by stereomicroscope (Motic, China) at 20 X magnification to check that there were no voids in the sealer, and the root canal had round shape see Fig. (1). If there was any void in the sealer, and\ or the canal was not round in shape, the sample of this section was omitted from the study, and replaced by another sample, which would be prepared in the same manner as mentioned above.…”
Section: Methodsmentioning
confidence: 99%